2008
DOI: 10.1002/jso.21181
|View full text |Cite
|
Sign up to set email alerts
|

Does chemotherapy increase morbidity and mortality after pneumonectomy?

Abstract: PCT does not significantly increase postoperative morbidity and early mortality after pneumonectomy in our experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…A study by Krasna and colleagues 18 demonstrated 5-year survival after neoadjuvant therapy of 35%, which they deemed acceptable. Alan and colleagues 19 showed 1- and 5-year survival of 71% and 40%, respectively, for the pneumonectomy alone group compared to 78% and 28%, respectively, for the group that received preoperative chemotherapy. These results suggest that neoadjuvant therapy does not adversely affect long-term survival and should be considered as part of a treatment plan for NSCLC patients, given its potential to convert a nonresectable tumor to a resectable stage, thereby allowing a favorable long-term survival, perhaps not possible otherwise.…”
Section: Discussionmentioning
confidence: 97%
“…A study by Krasna and colleagues 18 demonstrated 5-year survival after neoadjuvant therapy of 35%, which they deemed acceptable. Alan and colleagues 19 showed 1- and 5-year survival of 71% and 40%, respectively, for the pneumonectomy alone group compared to 78% and 28%, respectively, for the group that received preoperative chemotherapy. These results suggest that neoadjuvant therapy does not adversely affect long-term survival and should be considered as part of a treatment plan for NSCLC patients, given its potential to convert a nonresectable tumor to a resectable stage, thereby allowing a favorable long-term survival, perhaps not possible otherwise.…”
Section: Discussionmentioning
confidence: 97%
“…в 2015 г., посвящен дополнительному укрытию культи бронха после пневмонэктомии. Авторы оценили 21 работу из электронных баз данных, опубликованную за период с 1999 по 2012 г. В анализ вошли 3879 пациентов, из которых у 1774 (45,7%) было произведено дополнительное укрытие культи главного бронха [16,31,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Отбор пациентов для принятия решения о дополнительном укрытии культи бронха не производился случайным образом: в некоторых работах критерии не были указаны, в то время как в большинстве публикаций отмечено укрытие культи главного бронха после правосторонней пневмонэктомии, после которой риск возникновения бронхоплеврального свища считается традиционно высоким.…”
Section: Reviews Of Literatureunclassified